Utilization of Geogebra Application as Learning Media in Learning The Three-Dimensional to Increase Students' Interest in Learning - Widyastiti, Maya; Yanti, Yusma; Sumarsa, Amar; Durrotul Faizah, Layla (Hipotenusa: Journal of Mathematical Society, 2024)
This activity aims to describe students' interest in learning, learning outcomes, and the benefits of using GeoGebra in learning the three-dimensional. The data collected were analyzed using descriptive analysis. The research subjects were 59 students of SMA Negeri 1 Megamendung. Data collection techniques used tests and questionnaires. This research consists of 2 cycles. In cycle 1, the results obtained based on students' interest in learning showed that on average students strongly agreed 18.6%, agreed 31.1%, moderately 44.3%, and disagreed 5.9%. In cycle 2 after using the GeoGebra application, student interest increased to strongly agree 30.9%, agree 48.7%, moderately 18.6% and disagree 1.7%. Based on the learning outcomes in cycle 1, it shows 42.37% of students can solve problems well, while in cycle 2 there is an increase in the percentage of learning outcomes to 56.59%. Based on the results of the above analysis, it can be concluded that GeoGebra is very useful as a learning media and there is an increase in student interest and learning outcomes in learning the three-dimensional using GeoGebra.